Climate zone influences the effect of temperature on the day of artificial insemination on fertility in two Iberian sheep breeds - Abecia, Jose Alfonso (2017)
The aim of this study was to determine the effect of temperature on the day of artificial insemination (AI) on fertility, and to study how climate zone of the farm may modify this effect, in two breeds of sheep that are reared on the Iberian Peninsula on four farms located within one of three climate zones, based on the Köppen Climate Classification. A total number of 1,931 AI were studied from Spanish farms of the Rasa Aragonesa (RA) (July) and Churra (CH) (June) breeds. Farms were categorized as Köppen BSk (Farm BSk-RA; n=229), and Köppen Cfb (Cfb-RA; n=372), Köppen Csb (Csb-CH; n=908), and Köppen Cfb (Cfb-CH; n=422). Mean, maximum, and minimum temperatures (°C) were recorded, and thermal amplitude (maximum-minimum temperatures) calculated. Each set of temperature data was distributed between percentile-groups (≤50% and >50%), below or above the median. Temperatures at AI were higher (P<0.05) among successful inseminations than failed inseminations at the two Cfb farms. At the other two farms, temperatures on the day of AI were lower (P<0.05) among ewes that became pregnant than those that did not. At the two Cfb farms, fertility rates of the ≤50 and >50 percentile groups indicated that inseminations performed when temperatures were within the >50 percentile had a higher proportion (P<0.05) of ewes that became pregnant than did those in the ≤50 group. At the Cfb farms Odds Ratio OR were statistically significant and >1 for one or more of the meteorological variables under study; meanwhile, in the other two climates, OR were <1 (P>0.05). In conclusion, the effects of temperature on fertility after AI differed depending on the climate zone in which the flocks were reared. The results have implications for the scheduling of insemination dates to achieve the maximal performances.